Ryuji Kunimatsu Guitar Arrangement on the Oblivion by Astor Piazzolla: A Critical Analysis - Indrawan, Andre; Albarsani, Noer Iskandar; Kustap, Kustap; Suryati, Suryati (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This study examined the characteristics of Kunimatsu’s guitar arrangements in Astor Piazzolla’s Oblivion by comparing aspects of musical form, melody, and harmony. As with other arrangements’ performances, the primary motif of Astor Piazzola’sOblivion melodic theme in Kunimatsu guitar arrangement has always been played differently from the original version. This performance phenomenon could responsibly risk blurring the identification of structural boundaries within its musical form. The purpose of this study is to prove the basic construction of Oblivion melody, including its form structure and rhythmic characteristics, by comparing Kunimatsu’s arrangements against the composer’s original score. This study uses musicological research methods. The approaches applied in studying this work are analytical, theoretical, and comparative. This study compares the two data to reveal the musical forms and the differences in the primary motive rhythmic characteristics. The results of this study are findings of the Oblivion musical forms in both publications and the differences in primary motives rhythmic patterns in both sources. The difference in musical form is impressive, possibly caused by the insertion of auxiliary members. As a result, Kunamitsu arrangement includes using the two-part song form, originally a three-part song form. With the revelation of the original melodic structure that is clear from the results of this study, the musicians who will present the Oblivion will at least have the essential reference in their interpretation. This research contributes to expanding studies in classical guitar performance and musical forms and new approaches in textual musicological analysis that are still infrequent.